Gamma-based nuclear fusion measurements at inertial confinement fusion facilities - Mohamed, Z. L.; Kim, Y.; Knauer, J. P. (Frontiers in Physics, 2022)
Experiments performed on an inertial confinement fusion (ICF) platform offer a unique opportunity to study nuclear reactions, including reaction branches that are useful for diagnostic applications in ICF experiments as well as several that are relevant to nuclear astrophysics. In contrast to beam-accelerator experiments, experiments performed on an ICF platform occur over a short time scale and produce a plasma environment with physical parameters that are directly relevant to big bang and/or stellar nucleosynthesis. Several reactions of interest, such as D(T,γ)^5He, H(D,γ)^3He, H(T,γ)^4He, and T(^3He,γ)^6Li produce high-energy gamma rays. S factors or branching ratios for these four reactions have recently been studied using various temporally-resolved Cherenkov detectors at the OMEGA laser facility. This work describes these detectors as well as the current standard technique for performing these measurements. Recent results for reactions D(T,γ)^5He, H(D,γ)^3He, H(T,γ)^4He, and T(^3He,γ)^6Li are reviewed and compared to accelerator-based measurements. Limitations associated with implosion experiments and use of the current standard gamma detectors are discussed. A basic design for a gamma spectrometer for use at ICF facilities is briefly outlined.